Effect of Vitamin D on bone formation and resorption: Mathematical modeling approach - Sahattaya Rattanamongkonkul (2018)
We study the effect of Vitamin D on bone formation and resorption processes by developing a system of nonlinear differential equations. The model accounts for the serum level of vitamin D, the number of active osteoclastic cells and the number of active osteoblastic cells. It is then investigated both theoretically and numerically. The numerical result shows that the model can exhibit a periodic behavior for the parameters chosen to satisfy the conditions that we derived theoretically in conforming to the pulsatile serum level of vitamin D which has been observed clinically.